2011
DOI: 10.1136/gutjnl-2011-300306
|View full text |Cite
|
Sign up to set email alerts
|

Visceral hypersensitivity in endometriosis: a new target for treatment?

Abstract: Visceral hypersensitivity is extremely common in endometriosis and could be intensifying the pain. This finding might explain why mildly affected individuals often complain of severe symptoms out of proportion to the extent of their disease. This study has introduced a completely new concept into the understanding of pain in endometriosis and could open up new opportunities for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 51 publications
4
53
0
2
Order By: Relevance
“…A study conducted to evaluate visceral hypersensitivity using a rectal balloon reported a lower pain threshold in women with endometriosis compared to those without the disease (Issa et al, 2012). Although there was no difference in the VAS pain score between the groups, the reduction in the pain threshold found in women with endometriosis is in agreement with reports from other studies.…”
Section: Discussionsupporting
confidence: 87%
“…A study conducted to evaluate visceral hypersensitivity using a rectal balloon reported a lower pain threshold in women with endometriosis compared to those without the disease (Issa et al, 2012). Although there was no difference in the VAS pain score between the groups, the reduction in the pain threshold found in women with endometriosis is in agreement with reports from other studies.…”
Section: Discussionsupporting
confidence: 87%
“…Accumulating evidence supports a potential causal relationship between endometriosis and these functional pain symptoms, viscero-visceral sensitization and neurogenic inflammation might be a plausible explanation for these frequently coexisting conditions. 47,57,58 The uterus shares the same visceral innervation with the rectum and urinary bladder and a neural cross-talk among these organs is required for their physiological activities. 59,60 In fact, animal studies revealed that a subpopulation of TRPV1/TRPA1 expressing sensory neurons in the dorsal root ganglia collect nociceptive input from adjacent organs including mutual uterine-rectal, uterine-vesical and rectal-vesical neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In this class, immunomodulators such as interferon alpha 2 (IFN- α 2) and tumor necrosis factor (TNF) – α inhibitors have been tested in animal models [99]. In one study [100], visceral sensitivity was measured in endometriosis patients and compared with patients with irritable bowel syndrome (IBS) and identified that patients who had pain associated with endometriosis had greater visceral hypersensitivity compared to IBS patients. This not only gives a way to differentially diagnose endometriosis patients but also provides a novel target for therapy of endometriosis.…”
Section: Future Perspectivesmentioning
confidence: 99%